FTP in cycling: functional or fictional threshold power? - Caen, K. (Journal of Science and Cycling, 2023)
Functional threshold power (FTP) is a very popular metric in recreational and competitive cycling to evaluate, monitor and predict performance. This "threshold" is defined as the power output that a rider can maintain for one hour and is mostly determined by calculating 95% of the mean power output performed during a 20-min time trial. The popularity of FTP mainly originates from its practical feasibility, however, the scientific basis of this concept can be questioned. In this presentation, the physiological meaning of FTP and its relationship to other threshold concepts, such as critical power and the maximal lactate steady state, will be critically evaluated. Based on the most recent insights from literature, both the advantages and disadvantages of utilizing FTP in research and practice will be delineated.